Utilising blockchain technology and federated learning on the internet of vehicles for the preservation of security and privacy: systematic review - Alwash, Wisam Makki; Aydin, Muhammed Ali; Balik, Hasan Huseyin (INDERSCIENCE ENTERPRISES LTD, 2024)
In the field of the IoV, connected vehicles utilise network connections to improve transportation efficiency and safety. This will give rise to a range of vulnerabilities, specifically advanced cyber-attacks. These breaches will interrupt the normal functioning of vehicles and pose a significant hazard to the safety of passengers. This paper explores and reviews systematically the dual application of blockchain technology and FL as a fortified defence mechanism within the IoV ecosystem. This article presents illustrations of the risks present within the IoV domain and evaluates the efficacy of existing blockchain and FL methodologies, outlined in several papers, in addressing these potential challenges, particularly in the field of security and privacy. The paper provides an analysis of the advantages, limitations, and factors associated with these technologies in the context of maintaining the security and privacy of the IoV.
Keywords: internet of vehicles; IoV; cyber-attacks; security; privacy; blockchain; federated learning; FL; ENABLED INTERNET; SCHEME; AUTHENTICATION; NETWORKS; Computer Science